Relação jornada de trabalho e trabalho decente: entre a eficácia econômica e o retrocesso social. - Cabral., Monara Michelly de Oliveira (2013)
This work is concerned about the study of the proposed reduction in working hours without reducing wages as viable as the embodiment of the dignity of the worker, as well as a way of contributing to economic progress, this coupled with the social value of the work. For the development of this mostly qualitative research, it was used a dialectical method to approach the topic. As methods of procedure, were used historical and interpretive methods. It was undertaken as a research technique the indirect documentation, through bibliographic research. In a context of exploitation of the human labor by capital, where the question of labor time is a highlight, there is a necessity of labor relations humanization. In order to protect human dignity by achieving the fundamental rights of workers, it is important the request in reduction of the journey. It is claimed that the implementation of the measure promotes the worker life quality, allowing free time for leisure, family life, relax, professional qualification, and presents itself as an effective alternative to avoid unemployment. The topic is quite controversial, resulting in a true divergence between antagonistic forces of opposite social groups, with workers at one side, vindicating the right to a decent work with appropriate journey, that assure the protection of their physical and psychological integrity. On the other hand, there are the employers, who are against the implementation of the reduction, and allege negative economic impacts for their activities, and consequent loss of competitiveness due to increased social costs. Other countries experiences show that the implementation of the measure has not achieved the desired results as the creation of new jobs, but also did not cause economic backwardness. For the proposal to reduce the journey obtain succeed it is necessary that it be implemented by law and establishes limitations on work intensification and the overtime uses, because those mechanisms prevent the new signings and, consequently, undermine the advances in unemployment combat. The reduction of the working day is shown as an appropriate way to achieve human dignity, because the limited working hours, fair and reduced, provides the worker quality of life and enables its full development in the community in which he lives. This measure also provides positive results for the labor market and the economy, especially when it is implemented without salary reduction, which allows increasing the purchasing power of workers that are also consumers. The implementation of the measure is an important step towards the harmonization of economic and social values, revealing as an able way to put the economy on behalf of man.